Tajkistan: A Political and Social History - Nourzhanov, Kirill (ANU Press, 2013)
This book is a historical study of the Tajiks in Central Asia from the ancient times to the post-Soviet period. For millennia, these descendants of the original Aryan settlers were part of many different empires set up by Greek, Arab, Turkic and Russian invaders, as well as their own, most notably during the Middle Ages. The emergence of the modern state of Tajikistan began after 1917 under Soviet rule, and culminated in the promulgation of independence from the moribund USSR in 1991. In the subsequent civil war that raged between 1992 and 1997, Tajikistan came close to becoming a failed state. The legacy of that internal conflict remains critical to understanding politics in Tajikistan a generation later. Exploring the patterns of ethnic identity and the exigencies of state formation, the book argues that despite a strong sense of belonging underpinned by shared history, mythology and cultural traits, the Tajiks have not succeeded in forming a consolidated nation. The politics of the Russian colonial administration, the national-territorial delimitation under Stalin, and the Soviet strategy of socio-economic modernisation contributed to the preservation and reification of sub-ethnic cleavages and regional identities. The book demonstrates the impact of region-based elite clans on Tajikistan's political trajectory in the twilight years of the Soviet era, and identifies objective and subjective factors that led to the civil war. It concludes with a survey of the process of national reconciliation after 1997, and the formal and informal political actors, including Islamist groups, who compete for influence in Tajik society. "Tajikistan: A Political and Social History is the best source of information on this important country in the English language. Drs Nourzhanov and Bleuer present a comprehensive yet detailed account of the past and prospects of this emerging nation, and have filled one of the major gaps in Central Asian scholarship. This book must be read by those who wish to grasp the vagaries of Central Asia's evolving political and cultural landscapes." Reuel Hanks, Professor of Geography, Oklahoma State University, and Editor of the Journal of Central Asian Studies. "If Tajikistan is known outside its region, it is often for the civil war that gravely damaged it. This volume authoritatively provides the longer perspective to the unsettling events of the 1990s and skilfully explains them in terms of history, social structure, and sub-state identities. In addition to highlighting a wealth of local factors, it is insightful on the ways in which antagonists can be transformed into broader ethnic and regional blocs. Kirill Nourzhanov and Christian Bleuer are erudite guides to an understudied part of Central Asia, while astutely instructing us about larger patterns of state-society relations and their impact on the logic of conflict." James Piscatori, Professor of International Relations, Durham University.